Perceptions of parents, teachers, and five-year-old children on homework in traditional and progressive preschools - Valdes, Consuelo O.; Luna, Gisela de Asis. (2004)
This study entitled "Perceptions of Parents, Teachers, and Five-Year-Old Children on Homework in Traditional and Progressive Preschools", aims to investigate the perceptions of parents, teachers, and five-year-old students from both the traditional and progressive pre-schools regarding homework. A two-part survey questionnaire, the first being the multiple choice type and the second, the open-ended questions, were given to thirty parents and thirty teachers from selected traditional and progressive schools within Quezon City. An interview schedule as given to thirty, 5-year-old students from traditional and progressive preschools where the teachers and parents of the study came from. Both the survey and interview schedule dealt with the following types of homework, feelings regarding the difficulty of homework, effects of homework, benefits of homework, views on homework, drawbacks of homework in the amount of time spent on doing homework. The answers to the multiple choice questions were tallied while the answers to the open-ended questions were grouped together. The following findings revealed that the more common types of homework given to the children were the review and forward study type. Both the parents and teachers, on the other hand, had the following perceptions: In terms of the level of difficulty, they think the homework given is simple and motivating for the children's age level. In terms of reasons, homework helps the children learn better. Also, homework is done because the children themselves like the work given the work given to them. In terms of effects, it makes the children feel excellent because they can do something by themselves. In terms of benefits, homework serves as a tool that gives the teachers and parents an opportunity to know their children's progress in school. On the other hand, the drawback perceived by the parents and teachers was that homework is stressful when lengthy. It deprives the children time for playing and/or watching televisions. In terms of length, as perceived, homework is done within the range of fifteen (15) to thirty (30) minutes. On the basis of these findings, the following recommendations were presented: a) homework given to students must be able to sustain their interest; b) it should be aimed at enhancing performance; c) it should have a direct relation to the lessons of the day, reinforcing what they have learned in school. Other recommendations are d) homework formulated should strengthen parent-child bonding; e) homework should also be able structured in such a way that it allows the child to do his/her homework in his/her own; f) homework should enable the parents and the teachers will be enabled to discern whether the students have indeed learned the lessons taken up. Finally, in the light of the students' and parents' observation that the homework given is time consuming, it would be recommended that g) the teacher give homework that should be just enough to allow the child to have time for his other activities.
Thesis (M.F.L.C.D.)--University of the Philippines, Diliman.
Keywords: Homework -- Philippines -- Quezon City; Education, Preschool -- Philippines -- Quezon City